Controladores auxiliares de frequência para o restabelecimento de microrredes ilhadas com alto nível de inserção de geração eólica - Bordignon, Andrei (2017)
The diffusion of distributed generation and microgrids, as well as the growing expansion of renewable energy, like wind power, bring challenges and opportunities related to the operation and control of electrical power systems. In systems exposed to islanded operation, the black start capability is fundamental to restore the energy supply after the occurrence of a blackout. The black start is usually a difficult operational event, since significant power unbalances may occur in the system. The present work proposes operational and control strategies that make possible the black start of wind-diesel microgrids with high penetration level of wind generation, without the adoption of energy storage systems. The proposed control approach is based on two supplementary control loops for a fully rated converter wind turbine, which enable the wind unit to contribute to the frequency regulation during the black start of a stand-alone system. Both the proposed controllers employ the system frequency error as input signal and act only when the system loads are energized. One of the supplementary controllers seeks to extract kinetic energy from the wind turbine, by modifying the speed reference of the wind turbine in the typical control loop of the rotor-side converter. The second supplementary controller is designed to temporarily extract electrical energy from the DC-link capacitor, by acting in the reference of the DC-link voltage in the typical control loop of the grid-side converter. The energy extracted from the wind turbine and DC-link capacitor is injected into the grid to mitigate the power unbalance caused by the load energization. Thus, the proposed control strategies prevent excessive frequency drops during the load energization of low inertia stand-alone systems in restoration procedures. The design of the proposed controllers was performed by a genetic algorithm optimization technique. The performance of the system is compared in two different operation modes, diesel generator operating in Vf control mode and wind generation unit operating in Vf control mode. Results obtained by nonlinear time domain simulations demonstrate the effectiveness of the proposed control approach.